2016
DOI: 10.1002/nag.2540
|View full text |Cite
|
Sign up to set email alerts
|

Numerical evaluation of three non‐coaxial kinematic models using the distinct element method for elliptical granular materials

Abstract: SUMMARYThis paper presents a numerical evaluation of three non-coaxial kinematic models by performing Distinct Element Method (DEM) simple shear tests on specimens composed of elliptical particles with different aspect ratios of 1.4 and 1.7. The models evaluated are the double-shearing model, the double-sliding free-rotating model and the double slip and rotation rate model (DSR 2 model). Two modes of monotonic and cyclic simple shear tests were simulated to evaluate the role played by the inherent anisotropy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…[20][21][22][23][24][25]. The DEM has also been applied to correlate the macro-and micromechanical performances of geomaterials [15,26,27]. Thornton [26] relates the normal and tangential contact forces to the stress tensor, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25]. The DEM has also been applied to correlate the macro-and micromechanical performances of geomaterials [15,26,27]. Thornton [26] relates the normal and tangential contact forces to the stress tensor, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It has been concluded that the theory may be a viable law to describe the deformation of granular materials. The discrete element method has been employed in [21] to show that the model [22] for plastically incompressible materials provides a reasonable continuum mechanics description of the behavior of some granular materials. The present paper adopts the double shearing and rotation model proposed in [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is a non-coaxial theory, since it does not assume the principal axes of the stress tensor and the rate-of-strain tensor coincide. Applications of the double-shearing theory to problems in granular flow have been documented throughout the literature [16][17][18][19][20][21][22][23][24]. The theory itself is closely related to other well-studied non-coaxial kinematic models for granular flow [25][26][27][28][29], which themselves have been studied in detail over the past decades [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Applications of the double-shearing theory to problems in granular flow have been documented throughout the literature [16][17][18][19][20][21][22][23][24]. The theory itself is closely related to other well-studied non-coaxial kinematic models for granular flow [25][26][27][28][29], which themselves have been studied in detail over the past decades [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%